2016
DOI: 10.1038/srep28118
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-resolved depth profile of strain and cation intermixing around LaAlO3/SrTiO3 interfaces

Abstract: Novel behavior has been observed at the interface of LaAlO3/SrTiO3 heterostructures such as two dimensional metallic conductivity, magnetic scattering and superconductivity. However, both the origins and quantification of such behavior have been complicated due to an interplay of mechanical, chemical and electronic factors. Here chemical and strain profiles near the interface of LaAlO3/SrTiO3 heterostructures are correlated. Conductive and insulating samples have been processed, with thicknesses respectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Such information is recently becoming available from MEIS studies by Zaid et al 2 However, the gradual interdiffusion profile is too complex to treat directly with first-principles simulations. A small concentration in a any given layer would require a much large 2D cell than we here can afford with present computational power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such information is recently becoming available from MEIS studies by Zaid et al 2 However, the gradual interdiffusion profile is too complex to treat directly with first-principles simulations. A small concentration in a any given layer would require a much large 2D cell than we here can afford with present computational power.…”
Section: Discussionmentioning
confidence: 99%
“…However it can be controlled by annealing and is assumed to make a negligible contribution for sheet carrier densities of order 10 13 e/cm 2 . There has also been ample evidence for some degree of interdiffusion, most recently through a Medium Energy Ion Scattering (MEIS) study by Zaid et al 2 . The gradual change in c/a ratio observed in these measurements could be well explained by models including a gradually changing interdiffusion model.…”
Section: Introductionmentioning
confidence: 99%
“…7 Novel behavior with the implication to cation intermixing has been observed at the interface of LaAlO 3 /SrTiO 3 heterostructures such as two dimensional metallic conductivity, magnetic scattering and superconductivity. 41 …”
Section: Ba Xmentioning
confidence: 99%
“…Along with numerous physical phenomena, perovskite oxide heterointerface systems boast complexities that rival high-T c superconductors. Oxygen growth pressure 26 27 28 , La/Al stoichometry 29 , and cation intermixing 30 31 are a few of known factors that can affect interfacial conduction in LAO/STO. Recently, scanning probe or scanning electron microscopy techniques showed that crystal domain boundaries in the STO layer of LAO/STO modify the local conductivity of the interface and create regions of striped potential modulations 32 33 34 .…”
mentioning
confidence: 99%